Implementation of Managerial Supervision and Teacher Motivation to Improve the Quality of Learning for Junior High Schools in Waway Karya District, East Lampung Regency - Muhammad Ihsan Dacholfany; Dwi Lasmini D; Iswati (LP. Ma'arif Janggan Magetan, 2022)
The quality of learning is the result of the results of teacher work motivation carried out by the teacher, performance improvement is influenced by factors of managerial supervision and teacher motivation and. The aims of this study were to analyze: (1) The influence of the implementation of managerial supervision on the quality of learning, (2) The effect of teacher motivation on the quality of learning, and (3) The effect of the implementation of managerial supervision and teacher motivation together on the quality of learning. The results of the analysis obtained in this study are as follows: (1) The influence of the implementation of managerial supervision on the quality of learning. This can be explained by the equation Ŷ = 80.240 + 0.119 X1. With the regression equation, it can be interpreted that if the implementation of managerial supervision on the quality of learning is 21.10%, (2) The effect of teacher motivation on the quality of learning can be explained by the equation Ŷ = 57.550 + 0.164 X2. With the regression equation, it can be interpreted that if the implementation of teacher motivation on the quality of learning is 14.10%, and (3) the influence between the implementation of managerial supervision and teacher motivation together on the quality of learning, can be explained by the equation Ŷ = 68.217 + 0.174 X1 + 0.142 X2. With the regression equation, it can be interpreted that if the implementation of managerial supervision and teacher motivation on the quality of learning is 25.60%. With the conclusion that the results of the research above are to find out the influence between the implementation of managerial supervision and teacher motivation together on the quality of learning in junior high schools throughout the Waway Karya District, East Lampung Regency